Solidarity, Memory and Identity - Owczarski, Wojciech; Cremasco, Maria Virginia Filomena (Cambridge Scholars Publishing, 2015)
In today's context of rapid socio-political changes, with deepening ethnic and religious conflicts on the one hand, and a diminishing feeling of identification with the community on the other, reflection on the idea of ""solidarity"" is very much necessary. This book provides answers to the following questions: ""What is the idea of solidarity today?""; ""How can it be defined?""; ""How has it evolved over recent decades?""; ""How does it manifest itself in social life?""; ""How is it reflected in the arts?""; and, above all, ""How does it relate to collective memory and identity?"" With this